Social Capital for Disaster Management - Sri Novita Lubis; Sudarto Ronoatmodjo (Nusantara Science and Technology Proceedings, 2023)
This scoping review investigates how social capital contributes to disaster management, using the bonding, bridging, and linking of the social capital framework of Szreter and Woolcock (2004). Disasters have significant adverse effects that threaten the loss of life, injury, disease, and environmental damage. Social capital is a potential resource that can help communities overcome impacts and efforts to reduce the risk of disaster, but the functioning of social capital in all phases of disaster management has not been a concern yet. This study has paid attention to how the role of social capital, including bonding, bridging, and linking, is explored at every stage of disaster management for all types of disasters which may be rare in disaster studies. This review was conducted by Arksey and O’Malley’s framework scoping review. Using relevant keywords, we searched Google Scholar, Scopus, PubMed, EBSCOhost, and PLOS ONE for the last 13 years (2010-2023). Inclusion criteria included Bahasa or English language and only scientific literature such as research, journal articles, and scientific publications. Articles not specifying and measuring social capital in a disaster context were excluded. The literature search generated 25 related articles, which were reviewed and analyzed. Fifteen studies used qualitative, eight used quantitative, and two used mixed methods. Research results showed that social capital covering bonding, bridging, and linking contributes to all phases of disaster management. This review highlights the importance of social capital as part of the public policy approach. For future research to get prospective evidence from analytic studies and explore the feasibility of interventions that build social capital for effective and efficient disaster management.